1995
DOI: 10.1016/s0194-5998(95)70010-2
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of the canalith repositioning procedure

et al.

Abstract: Thirty-six subjects with confirmed, unilateral benign paroxysmal positioning vertigo of at least 2 months' duration were randomly assigned to one of two treatment groups. After complete informational counseling and explanation of the posttreatment instructions, subjects were randomly assigned to receive either Epley's canalith repositioning procedure or a placebo maneuver. All subjects completed a daily diary for 1 month to document any dizzy spells and their adherence to the posttreatment instructions. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
145
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(161 citation statements)
references
References 13 publications
12
145
1
3
Order By: Relevance
“…The index of spontaneous remission found in Lynn et al 24 was of 27%. According to Vrabec 9 , there may be spontaneous resolution of BPPV by absorption of statoconia, but the factors responsible for induction or prevention are very poorly known.…”
Section: Discussionmentioning
confidence: 82%
“…The index of spontaneous remission found in Lynn et al 24 was of 27%. According to Vrabec 9 , there may be spontaneous resolution of BPPV by absorption of statoconia, but the factors responsible for induction or prevention are very poorly known.…”
Section: Discussionmentioning
confidence: 82%
“…Even considering the possibility of self-resolution when treated with canalith repositioning maneuver, BPPV progresses better in the first month after the procedure, a fact that benefits patients and minimizes the duration of symptomatology 1,18,25,28,40,43 . However, the performance of the maneuver does not show substantial benefits in the long-term follow-up, between 3 and 6 months, nor in relation to the possibility of recurrence, which seems to be more related with etiology of vestibular affections that are associated with BPPV than to the symptomatic treatment adopted 18,44,45 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the care recommended, he suggested sleeping in a seated position or with 45 o elevation of the head for 48 hours after the maneuvers. Other authors 27,28 , who were stricter, recommended elevated head for 7 days after the maneuver, period in which sudden head movements and those that triggered dizziness would be avoided; not to sleep over the affected ear, and not to look up or down 29 . There were still others that instructed patients to wear a neck collar to prevent head movements 24,30,31 , a procedure not followed in our service owing to previous studies that suggested that neck collar and bone vibrator did not interfere in the outcomes of treatment 5,44 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Post-maneuver instructions (These instructions include avoidance of quick head movements or lying on the pathologic side, keeping the neck erect, sleeping at a 45° angle [15]). …”
Section: Methodsmentioning
confidence: 99%